A Deep Look Into Erionite Fibres: an Electron Microscopy Investigation of their Self-Assembly - Matassa, Roberto (Sci Rep, 2015)
The exposure of humans to erionite fibres of appropriate morphology and dimension has been unambiguously linked to the occurrence of Malignant Mesothelioma. For this reason, a detailed morpho-structural investigation through Electron Microscopy techniques has been performed on erionite samples collected at two different localities, Durkee (ED) and Rome (ER), Oregon, USA. The sample from Rome has been also investigated after a prolonged leaching with Gamble’s solution (ER4G) in order to evaluate the possible occurrence of morpho-structural modifications induced by this Simulated-Lung-Fluid (SLF). Here we report how the micrometric erionite fibres evolve in irregular ribbon- or rod-like bundles as a function of different nano-structural features. The reasons for the observed morphological variability have been explained by considering the structural defects located at ED surface fibrils (bi-dimensional ribbons) and the presence of nontronite, an iron-bearing clay mineral embedding the ER fibrils (mono-dimensional rods). ER4G shows a decrease in width of the rod-like fibres due to their partial digestion by SLF leaching, which synchronously dissolves nontronite. The reported results represent a valuable background toward the full comprehension of the morphological mechanisms responsible for potentially damage of lung tissue through the potential relocation of fibers to extrapulmonary sites, increasing the carcinogenic risk to humans.